Gender equality in Swedish academia: Unpacking the toolbox - Silander, Charlotte (Journal of Praxis in Higher Education, 2023)
Gender inequalities persist among Swedish academic staff, and gender balance is especially skewed toward men in the most prestigious academic career positions, such as professorships. In this article, the measures used in Swedish universities to promote gender equality among academic staff are investigated and related to theories of gender. The study is based on interview survey data on gender and diversity policies from 14 Swedish universities with an actor–structure categorization of gender equality (GE) measures used in Sweden universities since 1990. This first comprehensive study of GE policy among Swedish universities provides unique data on what policies universities have in place and rejects the notion that individual measures are predominantly used to fight gender inequality. Universities mostly use structural measures to ‘fix’ the organization, but from this approach follows that those measures are often gender neutral and soft, indicating a strong belief in gender-neutral principles, and they might limit the effect of action.